Designing a Health Workload Analysis Application for Medical Records Personnel Based on Hypertext Preprocessor at Hospital Outpatient Registration - Devi Devi; Nina Rahmadiliyani (Lambung Mangkurat University, 2024)
The primary method for planning HRK needs is the ABK-Kes method, which involves planning HRK needs at both the managerial and service levels according to workload, thereby determining the necessary number of employees. This study aims to design a PHP-based ABK-Kes application for the Hospital Outpatient Registration (TPPRJ). This descriptive study provides an overview of the design of a health workload analysis (ABK-Kes) application for medical records personnel. Following this overview, the study uses the SDLC design model using the waterfall model. The steps in the waterfall model include planning, analysis, design, implementation, system evaluation, and user acceptance testing. The results indicate that hospitals currently use manual methods for calculating HRK with the ABK-Kes method. The designed ABK-Kes application uses the ABK-Kes method formula and is developed using the PHP programming language, adhering to proper coding standards. The application is tested using Blackbox testing, focusing on the functionality of each menu item within the application.